Two new species of the sharpshooter genus Desamera from northern Brazil (Insecta: Hemiptera: Cicadellidae) - Carvalho, Rachel A.; Mejdalani, Gabriel (Zootaxa, 2006)
Two new species of the Neotropical sharpshooter genus Desamera Young are described and illustrated from Brazil: Desamera eliasi sp. nov. from Amazonas and Rondônia States and D. paraensis sp. nov. from Pará State. Desamera is for the first time recorded from northern and westcentral Brazil. The two new species can be recognized mainly by the aedeagal morphology. The female genitalia in Desamera are for the first time described in detail. Additional notes on the only other known species of the genus, D. intersecta (Germar), are provided.